Steroid-sparing maintenance immunotherapy for MOG-IgG associated disorder. (14th July 2020) - Chen, John J.; Flanagan, Eoin P.; Bhatti, M. Tariq; Jitprapaikulsan, Jiraporn; Dubey, Divyanshu; Lopez Chiriboga, Alfonso (Sebastian) S.; Fryer, James P.; Weinshenker, Brian G.; McKeon, Andrew; Tillema, Jan-Mendelt; Lennon, Vanda A.; Lucchinetti, Claudia F.; et al.
Abstract : Objective: Myelin oligodendrocyte glycoprotein–immunoglobulin G (MOG-IgG) associated disorder (MOGAD) often manifests with recurrent CNS demyelinating attacks. The optimal treatment for reducing relapses is unknown. To help determine the efficacy of long-term immunotherapy in preventing relapse in patients with MOGAD, we conducted a multicenter retrospective study to determine the rate of relapses on various treatments. Methods: We determined the frequency of relapses in patients receiving various forms of long-term immunotherapy for MOGAD. Inclusion criteria were history of ≥1 CNS demyelinating attacks, MOG-IgG seropositivity, and immunotherapy for ≥6 months. Patients were reviewed for CNS demyelinating attacks before and during long-term immunotherapy. Results: Seventy patients were included. The median age at initial CNS demyelinating attack was 29 years (range 3–61 years; 33% <18 years), and 59% were female. The median annualized relapse rate (ARR) before treatment was 1.6. On maintenance immunotherapy, the proportion of patients with relapse was as follows: mycophenolate mofetil 74% (14 of 19; ARR 0.67), rituximab 61% (22 of 36; ARR 0.59), azathioprine 59% (13 of 22; ARR 0.2), and IV immunoglobulin (IVIG) 20% (2 of 10; ARR 0). The overall median ARR on these 4 treatments was 0.3. All 9 patients treated with multiple sclerosis (MS) disease-modifying agents had a breakthrough relapse on treatment (ARR 1.5). Conclusion: This large retrospective multicenter study of patients with MOGAD suggests that maintenance immunotherapy reduces recurrent CNS demyelinating attacks, with the lowest ARR being associated with maintenance IVIG therapy. Traditional MS disease-modifying agents appear to be ineffective. Prospective randomized controlled studies are required to validate these conclusions.